THE IMPACT OF COVID-19 ON LEGAL EDUCATION IN INDONESIA - Rifana Heningtyas; Sofyan Wimbo Agung Pradnyawan (Khairun Law Journal, 2022)
Indonesia is one of the countries infected with the Covid-19 pandemic. Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled "Race Against the Virus, the Indonesian Consumer Response towards COVID-19" revealed that as much as 50% of Indonesian people began to reduce activities outside the home, and 30% of them said that they planned to shop more frequently online. Likewise, teaching and learning activities are carried out from home and even work is done from home with the aim of reducing Covid-19 epidemic.Â